Utilization of Spent Bleaching Earth Waste in Soil-Lime Stabilization for Road Body Foundation Layers Based on Index Properties - Syarif Razhik Ghazali (Jurnal Inovasi Teknologi, 2024)
Spent Bleaching Earth (SBE) is a mixed material between bleaching earth and organic compounds derived from bleached crude oil. In addition, spent bleaching earth still contains a component of phosphoric acid. This phosphoric acid comes from the degumming process which is brought to the bleaching process by oil. According to Government Regulation Number 22/21 concerning Implementation of Environmental Management and Protection, this spent bleaching earth is classified as non-B3 waste depth. Chemical stabilization is by mixing chemicals into the soil material which causes a chemical reaction to occur between the mixing material and the soil which will produce new materials that have better quality. From the results of the physical properties experiment, it was found that the mixture with the optimum value for soil-lime stabilization was 10% SBE.